Efektivitas Penerapan Tracer Terhadap Pengendalian Kejadian Missfile Rekam Medis Di UPTD Puskesmas Rendang - Ni Luh Ayu Winda Mahayani; Agus Donny Susanto; Dylla Hanggaeni Dyah Puspaningrum (UHN IGB Sugriwa Denpasar, 2023)
UPTD Puskesmas Rendang has not applicated a medical record tracer (exit instructions) so that there are still misplaced or no medical records found on the storage rack that caused missfile. Based on a preliminary study conducted in December 2021, it was found that the percentage of missfile events was 10.53% of 1,680 medical records. Puskesmas Rendang requires a medical record tracer that could overcome the problem of medical record missfiles. The purpose of this study is to design a medical record tracer and measure the effectiveness of the application of the tracer. The research design used is One Group Pretest-Postest Design, which is to measure the number of missfile events before and after the application of the medical record tracer. The results of this study are using a questionnaire test with a Likert scale, the results obtained are 85% whose feasibility can be categorized as